Dostoevsky's The idiot and the ethical foundations of narrative : reading, narrating, scripting - Young, Sarah J. (Anthem Russian and Slavonic studies., 2004)
"Provides an innovative theoretical framework for an analysis that integrates structural and narratological considerations with thematic (religious and ethical) aspects, by focusing on the characters' interactivity as the most fundamental level on which the ethical systems of the novel are enacted. Examines the questions of what ethical bases are put forward by the novel, what faith-issues and philosophical world-views they derive from, and how, in terms of structuring and narration rather than simply thematically, they are presented in the novel ... Through the concept of scripting, the author shows how the ethical becomes the foundation for the narratological in The idiot"--Page 4 of cover